Patients and Health Professional's Perspective of Functional Mobility in Parkinson's Disease - Bouça-Machado, Raquel; Gonçalves, Nilza; Lousada, Inês; Patriarca, Maria A.; Costa, Patrícia; Nunes, Raquel; Dias, Susana; Caldas, Ana Castro; Valadas, Anabela; Lobo, Patrícia Pita; Guedes, Leonor Correia; Rosa, Mário M.; et al. (Frontiers in Neurology, 2020)
Background: Functional mobility (FM) is the person’s ability to move to accomplish daily living tasks and activities. FM limitations are common in Parkinson’s disease, increase with disease progression and can be highly disabling. Although several studies in PD field use this concept, only recently, a formal definition has been proposed. Objective: We aimed to explore patients’ and health professionals’ perspectives of FM in PD. Methods: A focus group methodology has been used. Four focus groups, with a total of ten patients and ten health professionals, were performed. Six patients were early-stage and four advance stage. The health professionals’ group was composed of five neurologists and five physiotherapists. The suitability of the new concept, the impact of FM limitations in PD patients’ daily routine and the potential benefit of walking aids have been discussed. Results: All participants were able to provide a spontaneous definition of FM, matching with the proposed concept. All agreed that PD affects patients' FM, increasing the limitations with disease progression, and with the existence of a serious prejudice with walking aids that hinders its use. Early-stage patients’ perspective seems to be more in line with neurologists’ perspective, while the views of advanced-stage patients were closer to physiotherapists’ views. Conclusion: FM concept was considered as intuitive and useful. FM limitations have an important physical and social impact in the advance stage of the disease. Although patients and health professionals acknowledge walking aids benefit improving patients’ FM, the prejudice associated with this type of tools, limits its recommendation and use.